ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PERSAMAAN GARIS LURUS BERDASARKAN TAHAPAN NEWMAN - Bernadeta Buik; Hermina Disnawati; Justin Eduardo Simarmata (Universitas Islam Sumatera Utara, 2022)
The purpose of this research was to determine the types of errors and the causes of students in solving math story problems with straight-line equations based on Newman's analysis. This study used the descriptive qualitative method. The students who were the subjects of the research were three students of class VIII-B of SMP Negeri 1 Atap Obor which were taken from a total of 19 students. The instrument used was a written test question with a total of five description questions while the interview technique was carried out with selected students to ascertain the types of errors made in solving story questions. Data analysis includes data reduction, data presentation, and concluding. The results showed that three subjects were randomly selected based on the type of error Newman's analysis as follows: the first subject (S1) represented students in making mistakes in four stages, including the reading stage (T1), the problem understanding stage (T2), process skills (T4), and the final answer writing stage (T5). The mistakes made by the second subject (S2) who represent students in making mistakes in three stages, including the stage of understanding the problem (T2), the stage of process skills (T4), and the stage of writing the final answer (T5). The mistakes made by the third subject (S3) who represent students in making mistakes in the three stages, including the reading problem stage (T1), the process skills stage (T4), the final answer writing stage (T5).